2009
DOI: 10.2298/sos0902193l
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and fibre matrix interface characteristics of Cu/C(Fe) composite

Abstract: Cu/C composites were successfully fabricated by three step electro-deposition. The effects of hot pressure temperature and alloy element Fe on the interface characteristic of Cu/C composite were investigated. The results showed that the hot pressure temperature and interface characteristic have a great effect on mechanical properties of the composite. The tensile strength and hardness increase firstly and then decrease with the increasing of hot pressure temperature, and a tensile rupture appears when the hot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It was noted that the micro hardness increased according to sintering temperature. The surface of the samples on which the micro hardness values were measured was related to the density due to compacting for P/M samples, powder lubrication condition and mechanical properties of the powder [32,[42][43][44][45][46]. It can be concluded that the micro harness was directly related to density and inversely related to porosity.…”
Section: Tab Imentioning
confidence: 99%
“…It was noted that the micro hardness increased according to sintering temperature. The surface of the samples on which the micro hardness values were measured was related to the density due to compacting for P/M samples, powder lubrication condition and mechanical properties of the powder [32,[42][43][44][45][46]. It can be concluded that the micro harness was directly related to density and inversely related to porosity.…”
Section: Tab Imentioning
confidence: 99%
“…According to Li et al [58], Cu/C composites were successfully fabricated by three step electrodeposition. The effects of hot pressure temperature and alloy element Fe on the interface characteristic of Cu/C composite were investigated.…”
Section: Electrodeposition Of Copper Nanocompositesmentioning
confidence: 99%
“…MMCs show several improvements, such as lower and tailorable CTE, high heat dissipation capability, low weight, and high dimensional stabilities at an elevated temperature. More specifically, there is great interest in MMCs based on Cu with a broad range of different reinforcements [3,7,8]. Since carbon (C) reinforcements have high thermal conductivity and low thermal expansion, MMCs reinforced with C can also present good TC and CTE [4].…”
Section: Introductionmentioning
confidence: 99%